2021
DOI: 10.20867/thm.27.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Illustrating the Perception of Students Towards Autonomous Service Robots in the Tourism Industry: An Exploratory Study

Abstract: Research purpose – The purpose of the study was to explore the students’ perceptions towards autonomous service robots, using interviews and, in a novel manner, also their drawings, to generate data. The paper contributes to current knowledge claims around the Techno-Economic Paradigm by providing a greater understanding of, and student response to, autonomous service robots. Additional insights were gained on transformational skills set for tourism practitioners. Design/Methodology/Approach – A qualitative ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The findings indicated that African countries are trying to tap 4IR technologies and are currently aware of their potential for sustainable development. According to Wakelin-Theron (2021), the world has changed how people do their work with the introduction of 4IR technologies. 4IR technologies are acknowledged as the potential ignition that will fuel the attainment of SDGs in many developing countries in Africa.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…The findings indicated that African countries are trying to tap 4IR technologies and are currently aware of their potential for sustainable development. According to Wakelin-Theron (2021), the world has changed how people do their work with the introduction of 4IR technologies. 4IR technologies are acknowledged as the potential ignition that will fuel the attainment of SDGs in many developing countries in Africa.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Although prior studies largely focus on the guest and operator perspectives, educators are important stakeholders too and it is important to acknowledge their role in shaping the sustainable employability skills of next-gen hospitality graduates (Pillai et al, 2021). Industry 5.0 applications provide increased business outcomes and performance, enhanced service Next generation employability assurance and underpin the belief that humans are more powerful than robots in terms of social intelligence (Wakelin-Theron, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These employees are expected to have a wide variety of skills and attributes to work in the changing tourism industry that is often volatile, unknown, complex, and ambiguous (VUCA) (Wakelin-Theron et al, 2019). It is, however, possible to mentor them to become competent employees in a changing environment (Satterly et al, 2018;Wakelin-Theron, 2021). Millennials are often younger than some of their managers and supervisors and have not experienced difficult times in an environment that is not conducive, and these chefs are not as resilient as the older generations who have learnt how to handle stressful situations (Liebenberg & Moore, 2018).…”
Section: The Millennial Executive Chefs and Chefs De Partiementioning
confidence: 99%
“…Management needs to monitor staff, alleviate workplace pressure, and act before the situation becomes unmanageable. By providing support, resources as well as opportunities for growth and additional learning in a positive social and work environment that promotes productivity, improves mental health, and reduces job stress is created (Ungar, 2019;Wakelin-Theron, 2021). Numerous individuals experience stress but have the necessary resources and support not to experience burnout (Ungar, 2019).…”
Section: Resources and Supportmentioning
confidence: 99%